2017
DOI: 10.5535/arm.2017.41.3.441
|View full text |Cite
|
Sign up to set email alerts
|

A New Instrument for Measuring Tibial Torsion in Pediatric Patients

Abstract: ObjectiveTo develop and test the validity and reliability of a new instrument for measuring the thigh-foot angle (TFA) for the patients with in-toeing and out-toeing gait.MethodsThe new instrument (Thigh-Foot Supporter [TFS]) was developed by measuring the TFA during regular examination of the tibial torsional status. The study included 40 children who presented with in-toeing and out-toeing gaits. We took a picture of each case to measure photographic-TFA (P-TFA) in the proper position and to establish a crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In this study, there were no significant differences in tibial torsion in people with GJH compared to the control groups. Similar results were obtained by Jeon et al [19]. The high values of standard deviation (SD) indicate the high individual variability of the tibial torsion in participants.…”
Section: Tibial Torsionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, there were no significant differences in tibial torsion in people with GJH compared to the control groups. Similar results were obtained by Jeon et al [19]. The high values of standard deviation (SD) indicate the high individual variability of the tibial torsion in participants.…”
Section: Tibial Torsionsupporting
confidence: 87%
“…In the literature, no studies were found about the assessment of the rotation in the hip joints, the axis of the lower limbs, tibial torsion, and arches of feet in subjects with GJH at different ages. This issue seems to be important for posturology and the causes of gait disorders [19]. Sass et al [33] claimed that rotational and angular disorders of the lower limbs are the most common disorders in children whose therapy is based on conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The angle between the second ray and the thigh axis was regarded as the thigh-foot angle. The negative value refers to the internal rotation of the tibia, whereas the positive value refers to the external rotation [ 20 ]. For the femoral torsion deformity, internal and external hip rotation was measured with the patient prone and the knees flexed to 90°.…”
Section: Methodsmentioning
confidence: 99%